THE EFFECT OF NOISE ON WORK FATIGUE IN AN OIL AND GAS INDUSTRY - Okto Hebrani; Sandra Madonna; Prismita Nursetyowati (Universitas Trisakti, 2018)
Aim: The purpose of this study is to determine the effect of noise on work fatigue at Central Processing Plant (CPP) Gundih Completed. Noise is one of the causes of fatigue in the oil and gas industry. Methodology and Result: Noise is measured using a Sound Level Meter at 45 sampling points spread across two gas processing zones at CCP Gundih in Cepu is Utility zone and Main Process zone. The noise distribution pattern based on noise level in gas processing field of CPP Gundih made using Surfer 11 software. Measurement of fatigue using the Fatigue Measure Measurement Questionnaire and Subjective Self Rating Test questionnaire from Industrial Fatigue Research Comitte Japan. The results of this study prove that the Utility Zone at the sampling point 35 to 45 has a noise level of 74,229 dBa - 106,285 dBa, point 45 has passed the Noise Decree of Kepmenaker No. 51 of 1999, but overall the sampling point in the Utility zone has passed through Kepmenlh no. 48 in 1996. In the Main Process zone at sampling points 6 to 17 and 30 have passed the standard noise level Kepmenaker no. 51 of 1999 with a noise level of 85.967 dBa to 87.155 dBa and 85.146 dBa. Overall there are 4 sampling points that do not pass the standard noise level of Kepmenlh no. 48 of 1996 and Kepmenaker no. 51,1999 points 25, 26,31 and 33. Conclusion, significance and impact study: Noise affects fatigue based on several factors, including noise factor 39%, 32.1% weakening activity factor and physical fatigue factor 28.2%.